Development of mathematical model and optimization of GMA welding parameters of IS 2062 grade A steel weldments (Fracture and Structural Integrity, 2021)
In this experimental works, the effect of GMA welding process parameters, such as arc voltage, wire feed speed, and gas flow rate on the mechanical quality of IS 2062 structural steel of grade A has been studied. Process parameters play an important role in determining the weld quality. In this research work response surface methodology (RSM) technique via design expert (DOE) 12 version software was applied to determining the weld quality and also to develop a mathematical model that can predict the main effect of the above said parameters on weld quality i.e. toughness and hardness. A set of experiments has been conducted to collect the data using a central composite design and ANOVA was used to predict the impact of welding parameters on toughness and hardness and Comparison also made between the actual result and predicted value and from the result that is clear that toughness and hardness of weldment is significantly affected by arc voltage, wire feed speed, and follow by gas flow rate.
Keywords: response surface methodology (RSM); centre composite design (CCD); modeling; GMA welding; mechanical quality